Changing the Economics of Organic Waste Disposal Using Managed Ecosystem Fermentation - Calt, Edward A. (International Journal of Biotechnology for Wellness Industries, 2013)
Concentrated organic waste is a major societal problem. It is a disease vector, a source of groundwater contamination, as well as a source of greenhouse gases. Managed Ecosystem Fermentation (MEF) is a technology that converts this societal problem into an economic resource for the community. MEF is a fermentation process that uses over 3,000 species of microbes simultaneously to produce multiple high-value products used in industry and agriculture. The products include fertilizer, high-protein animal feed, volatile fatty acids, longer chain fatty acids, amino acids, enzymes, etc. The values of these products range from 50 to over 16,000 per ton. MEF is an adaptive system that processes non-homogeneous, non-sterile organic waste/s under non-sterile conditions. It converts the waste into industrial products in 24 hours using a microbial system that has worked for millions of years. It is the only known technology that can convert cellulose into protein. Society benefits from converting what is now a cause of disease, groundwater contamination and greenhouse gases into valuable products.